The roller chopping school: educational process technology (Semiárida, 2020)
Socioeconomic and productive processes that accompany cattle breeding in areas like the Planicie Este in Mendoza Province, demanding action lines of the institutions that meet function in these territories. Thus, through one of the most important tools of extension, education, attended the demand for knowledge of both producers and educational institutions. The systematization of experiences in rolling generated by producers and the National  Institute of Agricultural Technology (INTA), through information provided by the tests and extension activities, allowed to transform these experiences into systematic and communicable knowledge. Through a series of field meetings, seminars and conferences, producers, professionals and technicians from INTA, EEA headquarters Rama Caída, exchanged, discussed and agreed common criteria of problematic cattle farms in the province of Mendoza. The main topic discussed was the increased availability of natural grassland forage through techniques such as rolling. Was achieved to accompany and enhance research work of students, commensurate with their education development, achieving a significant integration between INTA and educational institutions. With all these activities, it was possible to approach the areas of investigation and extension of INTA and other institutions, generating a significant synergistic effect.
Keywords: Education; Roller chopping; Science Fair; Field Meetings; Technical Conference; Systematization of experiences